2009
DOI: 10.1007/s00464-009-0468-5
|View full text |Cite
|
Sign up to set email alerts
|

Peritonitis from peg tube insertion in surgical intensive care unit patients: identification of risk factors and clinical outcomes

Abstract: Approximately 5% of patients undergoing PEG insertion in the SICU require laparotomy for peritonitis and are more likely to die during the hospitalization. Higher BMI and a lower serum albumin level, by contributing to poor healing, increase the risk of peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…The combination of these 2 factors increases the likelihood of laparotomy by 25-fold. 103 Wound infections at the PEG site are common. A recent multicenter study identified 4 independent risk factors for peristomal infections including clinical institutionalization, size (15F Ͼ 9F), experience of the endoscopist (Ͻ100 procedures), and the existence of an underlying malignant disease.…”
Section: Safetymentioning
confidence: 99%
“…The combination of these 2 factors increases the likelihood of laparotomy by 25-fold. 103 Wound infections at the PEG site are common. A recent multicenter study identified 4 independent risk factors for peristomal infections including clinical institutionalization, size (15F Ͼ 9F), experience of the endoscopist (Ͻ100 procedures), and the existence of an underlying malignant disease.…”
Section: Safetymentioning
confidence: 99%
“…Secondly, as we have illustrated, fluoroscopy is much better at outlining the distended stomach when transillumination is not possible with the endoscope. Since BMI above 30 is a known risk factor for complications and mortality post tube placement [4], multiplanar imaging must be used to exclude viscera from the intended access path. A steep RAO view of the abdomen or true lateral view is helpful in identifying viscera intestinal components anterior to the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Lífhimnubólga var algengasti fylgikvillinn (2,7%) og var tíðni hennar svipuð hér og í öðrum rannsóknum (0,8-4%). 23 Lífhimnubólga eftir PEG-aðgerð kviknar ef PEG-slangan dregst út, gat kemur á magann eða ef magainnihaldið lekur inn í kviðarholið, og getur hún verið lífshaettu legur fylgikvilli. 23 Rannsóknir hafa sýnt að faekka má fylgikvillum við PEG-aðgerðir ef sjúklingar eru rétt valdir, fyrirbyggjandi sýklalyf eru notuð, reynsla laekna sem gera slíkar aðgerðir er góð og ef tveir laeknar vinna saman við aðgerðina.…”
Section: Umraeðaunclassified